Effect of Sappan Wood Ethanol Extracts (Caesalpinia sappan. L) to the Sperm Motility, Viability, and Concentration of Male Wistar Rats - Nadiyah Nadiyah; Andri Rezano; Sunarjati Sudigdoadi (Faculty of Medicine Universitas Padjadjaran, 2017)
Background: Idiopathic male infertility becomes an issue because of the limited management options and increasing number of infertile couples. Sappan wood (Caesalpinia sappan. L) is an herbal plant predicted to have fertility and spermatogenesis enhancing effects through antioxidant properties. This study aimed to observe the effects of sappan wood ethanol extract in improving sperm quality of male wistar rat based on sperm motility, viability, and concentration. Methods: This was an experimental laboratory study by using sappan wood ethanol extracts as material and male wistar rat as the experimental animal. Twenty-four adult male wistar rats were divided into 4 groups including rats which were treated with aquades, 30, 60, and 120 mg/kg/day/orally of ethanol extract of sappan wood, respectively, during 35 days. After this period, the animals were sacrificed. Then the epididymis were taken for samples to calculate sperm motility percentage, sperm viability percentage and sperm concentration. Comparison between control group and the treated group was analyzed by one-way Annova.Results: There were significant differences between the control group and the group with 120 mg/kg of sappan wood ethanol extracts in the percentage of motility (36.39% and 51.75%; p-value 0.001), viability percentage (55.36% and 66.63%, p-value 0.031), and sperm concentration (54.47 million/ml and 47.79 million/ml; p-value 0.001).Conclusions: The ethanol extract of sappan wood with a dose of 120 mg/kg for 35 days is able to improve sperm motility percentage, sperm viability percentage, and sperm concentration of male wistar rat. DOI: 10.15850/amj.v4n2.1078